1995
DOI: 10.1111/1523-1747.ep12317599
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and Quercetin Interact with Type II Estrogen Binding Sites and Inhibit the Growth of Human Melanoma Cells

Abstract: The mechanism of the antiproliferative activity of tamoxifen on melanoma cells in vitro and in vivo is poorly understood, as it is not mediated by the antiestrogenic properties of tamoxifen. Using a whole-cell assay and nuclear and cytosolic radio-binding experiments with [3H]-estradiol as tracer, we found that MNT1, M10, and M14 melanoma cell lines as well as primary tumors expressed type II estrogen binding sites that bind tamoxifen and the flavonoid quercetin with similar affinity (KD 10-25 nM). Cell count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 33 publications
6
54
0
5
Order By: Relevance
“…Given a di erent outcome of quercetin exposure depending on cell type and culture conditions, we asked what e ect quercetin would have on the growth of PalF cells. Indeed PalF cells do undergo growth arrest when exposed to quercetin concentrations (20 ± 100 mM) similar to those reported for established cells (60 ± 120 mM; Plauman et al, 1996) but considerably higher than for tumour cells (1 nM ± 1 mM; Scambia et al, 1993;Piantelli et al, 1995), con®rming that the genetic background of the cell determines at least in part its response to thē avonoid. During the ®rst 12 h of quercetin treatment at higher doses (50 and 100 mM) almost twice as many PalF cells are in S phase than untreated cells.…”
Section: Quercetin Inhibits Proliferation Of Palf Cellssupporting
confidence: 80%
See 1 more Smart Citation
“…Given a di erent outcome of quercetin exposure depending on cell type and culture conditions, we asked what e ect quercetin would have on the growth of PalF cells. Indeed PalF cells do undergo growth arrest when exposed to quercetin concentrations (20 ± 100 mM) similar to those reported for established cells (60 ± 120 mM; Plauman et al, 1996) but considerably higher than for tumour cells (1 nM ± 1 mM; Scambia et al, 1993;Piantelli et al, 1995), con®rming that the genetic background of the cell determines at least in part its response to thē avonoid. During the ®rst 12 h of quercetin treatment at higher doses (50 and 100 mM) almost twice as many PalF cells are in S phase than untreated cells.…”
Section: Quercetin Inhibits Proliferation Of Palf Cellssupporting
confidence: 80%
“…Thus it behaves as an initiator in a two stage in vitro cell transformation model (Sakai et al, 1990) and potentiates the carcinogenic activity of azoxymethane in rats (Pereira et al, 1996), but it inhibits the action of TPA in mice (Kato et al, 1983) and causes cell growth arrest in a variety of tumour or established cell types (Hosokawa et al, 1990;Ranelletti et al, 1992;Scambia et al, 1993;Piantelli et al, 1995;Avila et al, 1994;Plaumann et al, 1996). Its cytostatic e ect has prompted the proposal that quercetin be used as an anticancer agent .…”
Section: Quercetin Inhibits Proliferation Of Palf Cellsmentioning
confidence: 99%
“…The natural ligand for the type II EBS is methyl -p -hydroxyphenylactate (Makaveriech et al, 1988), and it is thought that these receptors can be occupied by flavenoid-like molecules (Piantelli et al, 1995). The type II EBS has a lower affinity but higher capacity for oestrogen than the classical oestrogen receptors -they have an apparent dissociation constant of around 20 nm for oestrogensand we found that nanomolar (10-100 nM) concentrations of 17p-oestradiol inhibited invasion.…”
Section: Discussionmentioning
confidence: 47%
“…This indicates the possible involvement of an alternative inhibitory mechanism. In this light, a type II EBS, distinct from the oestrogen receptor, was discovered (Sutherland et al, 1980) which can bind tamoxifen (although not the drug ICI 182,780) and may be induced in both oestrogen receptor negative breast cancer and melanoma cells inhibited by tamoxifen (Piantelli et al, 1995). Thus, one explanation for our data is that some of the actions of tamoxifen may have been as a result of its actions on a type II EBS rather than on a classical nuclear oestrogen binding site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation